دور الأنظمة العقابية الحديثة في معالجة الجريمة في الجزائر - منار صبرينة; إشوي عماد; منار فاطمة الزهرة (مجلة الاقتصاد والقانون, 2022)
The return of the offender to his crime after the completion of his sentence may explain the failure of care programs in its various forms, from overcrowding in prisons and friction between prisoners, which leads the prisoner to learn new methods and skills in this field of crime during the execution of the punishment. The punishment in itself is the punishment of society and the inferiority with which it meets, and marginalization even by his friends, which stands as a barrier to his social inclusion, closing the doors in his face will inevitably lead him to return to his crimes, even if the welfare and reform programs succeed in their various forms, which prompted modern penal jurisprudence to search for alternatives to penalties that deprive him of freedom, especially of short duration, because of the negative points that are more effective and at lower costs in order to reform the offender and bring back Socialize.
Keywords: crime; punishment; penal policy; reintegration; criminal behavior.